Effect of high-pressure treatment on emulsifying properties of soybean proteins - Puppo, Maria Cecilia (2005)
Modifications of emulsifying properties of soybean protein isolates (SPI) by high-pressure processing have been studied. SPI solutions at 10 g/l in two pH conditions: alkaline (pH 8: SPI8) and acidic (pH 3: SPI3) were treated by high-pressure at various pressure levels (200, 400 and 600 MPa for 10 min at 10 °C). Oil-in-water emulsions (30/70) were prepared with untreated and high-pressure treated SPI3 and SPI8. Emulsifying properties (oil droplet size, flocculation, interfacial protein concentration and composition) were evaluated. Pressure processing of SPI8 from 200 MPa induced a reduction of droplet size and an increase of depletion flocculation, not observed with SPI3. Bridging flocculation decreased and percentage of adsorbed proteins increased when pressure was applied, whatever the pH conditions. High-pressure treatment induced more ability to proteins, and particularly β-7S and A-11S polypeptides, to be adsorbed at the oil–water interface. At pH 3, high-pressure processing seemed to improve emulsifying properties that have declined due to acidification.